Association of anti-citrullinated peptide antibodies with the progression of aortic stenosis. (3rd October 2022) - Kim, A; Ji, E; Lee, S; Hong, S; Kim, D H; Song, J M; Kang, D H; Song, J K
Abstract: Background/Purpose: Aortic stenosis (AS) is common in an aging population, but disease activity biomarkers are lacking. The pathophysiology of calcific AS shares many similarities with atherosclerosis, including lipid deposition, inflammation, and calcification. Citrullination is a part of many chronic inflammatory processes and citrullinated proteins have been found within atherosclerotic plaque. Thus, we investigated whether the presence of anti-citrullinated peptide antibody, especially anti-CCP antibody, might be associated with AS. Methods: A retrospective observational study was conducted for 678 patients who underwent echocardiography and anti-CCP antibody test between April 2004 and July 2020. Anti-CCP antibody status was regarded as positive when concentrations exceeded the upper limit of normal (ULN), and any lower value was considered negative. The anti-CCP antibody-positive group was subdivided into two groups: low-positive for ≥ ULN but < the median, and high-positive ≥ the median value (Figure 1A). Also, aortic valve (AV) tissues were obtained from the patients with AS or not at the time of surgical aortic valve replacement or heart transplantation, who did not have rheumatoid arthritis. We analyzed the presence of citrullinated proteins in the AV by immunohistochemistry and Western blotting. Results: 241 (35.5%) subjects showed AV degeneration in baseline echocardiography. They had a higher anti-CCP antibody positivity rate (42.7% vs. 34.6%, p=0.035) than the subjects without AV degeneration. Of total patients, 331 (48.8%) subjects underwent follow-up echocardiography (median follow-up duration 4.6 years [interquartile range 2.0–8.0 years]). AS progression, which was defined as an increase of at least one grade in AS severity classification on follow-up echocardiography, was observed in 34 (10.3%) patients. The progression of AS occurred more in the high-positive group than in the low-positive or negative group (19.0% vs. 11.3% vs. 8.4%, respectively; p=0.041) (Figure 1B). In multivariate analysis, the high-positivity of anti-CCP antibody was an independent predictor of AS progression (Odds ratio: 2.312; 95% confidence interval: 1.006–5.310; p=0.048) (Figure 1C). Increased citrullination was visualized in areas with diseased AV compared with normal AV tissue by immunohistochemistry (Figure 2A, 2B) and Western blotting (Figure 2C, 2D). These results suggested the possible association with the citrullinated peptide-related inflammation process and the pathophysiology of AS. Conclusion: A positive result of anti-CCP antibody, especially with a high titer, was associated with AV degenerative change at baseline echocardiography. Also, anti-CCP antibody positivity was an independent factor for predicting the progression of AS. These findings suggest that citrullination can be a part of the pathophysiology of AS. Furthermore, the anti-CCP antibody can be a biomarker predicting AS progression. Further research will be needed. Funding Acknowledgement: Type of funding sources: None.